2020
DOI: 10.3389/fphar.2020.542405
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Investigation of miRNAs From Gastrodia elata Blume and Their Potential Function

Abstract: Gastrodia elata Blume (G. elata) is a valuable traditional Chinese medicine with neuroprotection, anti-inflammatory, and immune regulatory functions. MicroRNAs (miRNA) is a kind of endogenous noncoding small RNAs that plays distinctly important roles for gene regulation of organisms. So far, the research on G. elata is mainly focused on the pharmacological functions of the natural chemical ingredients, and the function of G. elata miRNA remains unknown. In this study, 5,718 known miRNAs and 38 novel miRNAs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…GEB protects the BBB by counteracting oxidative stress, decreasing neuroinflammation and inhibiting apoptosis, thereby showing promising neuroprotective properties in the acute phase of cerebral ischemia ( 40 , 41 ). However, as the pathophysiological mechanisms of IS are complex and the active components of GEB are not known, the underlying mechanisms that induce neuroprotection remain unclear ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…GEB protects the BBB by counteracting oxidative stress, decreasing neuroinflammation and inhibiting apoptosis, thereby showing promising neuroprotective properties in the acute phase of cerebral ischemia ( 40 , 41 ). However, as the pathophysiological mechanisms of IS are complex and the active components of GEB are not known, the underlying mechanisms that induce neuroprotection remain unclear ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gastrodia elata Blume is a kind of traditional Chinese medicine with many functions, including neuroprotection, immune regulation, and anti-inflammatory. 215 Gastrodia elata Blume derived Gas-miR01 and Gas-miR02 were detected in the cerebellum, cerebrum, hypothalamus, kidney, heart and spleen of mice by intragastric administration, meanwhile, both Gas-miR01 and Gas-miR02 can inhibit target gene of Homo sapiens A20, which was driven by NF-κB singing. 215 Dried nuts-derived miR-159a and miR-156c were present in exosome-like nut nanovesicles, and they downregulated the protein expression of Tnfrsf1a (mammalian TNF receptor superfamily member 1a), inflammatory markers, and dampen TNF-α signaling pathway in adipocytes and mice.…”
Section: Exogenous Mirnas and Human Diseasesmentioning
confidence: 96%
“…59 Gastrodia elata Blume derived miRNAs were also found to be associated with the cross-kingdom regulation of Homo sapiens genes. 215 Of emerging interest is the recently recognized role of plant-derived miRNAs in tumor proliferation and virus replication, 62 which indicates that they might serve as novel regulators of human disease caused by environmental pollutants. Currently, it was revealed that miRNAs from animals and plants can act in a noncell-autonomous manner and regulate gene expression in the host by exchanging information between species.…”
Section: Exogenous Mirnas and Human Diseasesmentioning
confidence: 99%
“…Transfect Gasmi R01 and Gas-mi R02 mimics to 293T cell significantly inhibited the expression of A20, which is an important feedback regulator of NF-kB-driven gene. Additionally, after gavage GE decoction to mice, high levels of Gas-mi R01 and Gas-mi R02 could be detected in mice serum, liver, brain, kidney, spleen, and reduced A20 expression (Zhou, 2018;Xia et al, 2020). These results suggested that GE miRNAs are a group of active ingredients in GE and may responsible for the well know antiinflammatory and immune regulation efficiency of Gastrodia elata.…”
Section: Anti-inflammationmentioning
confidence: 97%